Altered Serum Factor Vlll-Related Antigen (VIII: AGN)/von Willebrand Factor (VIII: vWf) in Haemophiliacs with Inhibitors to Factor VIII Procoagulant Activity (VIII: C) - Ballard, J O; Sanders, J C; Eyster, M E (Thrombosis and Haemostasis, 1981)
Inhibitors to factor VIII (anti-F VIII) developing in patients with classic haemophilia have apparent specificity for the factor VIII procoagulant activity (VIII: C), rather than the factor VIII-related antigen (VIII :AGN) and von Willebrand factor (VIII :vWf) regions of the factor VIII complex.Since procoagulant function is absent following in vitro clotting, but serum retains VIII: AGN/vWf properties, we searched for differences in VIII :AGN and VIII :vWf of inhibitor serum that might relate to the presence of anti-F VIII.Rocket immunoelectrophoresis and the washed platelet ristocetin assay were performed on the plasma and serum of nine haemophiliacs with inhibitors, 23 non-inhibitor haemophiliacs and six normal subjects. Unlike normal and non-inhibitor haemophilic sera, that from five of nine inhibitor patients demonstrated absent VIII : vWf and significantly lower VIII: AGN (p <0.05). Furthermore, VIII: AGN of faster mobility was detected on crossed immunoelectrophoresis of the sera of three inhibitor patients. Thrombin clotting of plasma from haemophiliacs with high titer anti-F VIII was associated with a greater loss of VIII: vWf than seen with non-inhibitor haemophilic plasma. This effect was independent of the presence of platelets.These data indicate that in vitro clotting is associated with alteration in the serum VIII: AGN/vWf of some haemophiliacs with anti-F VIII.
Keywords: Haemophilia A; Factor VIII inhibitor; Factor VIII complex; Serum factor VIII antigen and von Willebrand factor